Are virtual backgrounds during online learning distracting? An attention study using eye tracker technology - Regita Wijaya; Ari Widyanti; Rifko Rahmat Kurnianto (Knowledge Management & E-Learning: An International Journal, 2024)
During and after the Covid-19 pandemic, online learning has gained popularity. Video conferencing, such as Zoom, has become the new normal in almost every individual’s life. The purpose of this study is to observe the usage and preference of Virtual Background (VB) during video conferencing through a survey, whereas the effect of VB on attention during online meetings is evaluated through an eye tracker experiment. An online survey is conducted to observe the usage and preference of Indonesian users of Zoom in applied VB. Based on the most preferred VB, an eye tracker experiment was conducted to evaluate participants’ attention during online learning using the three most preferred VB: office VB, plain background, and thematic VB. Eye tracker parameters, including Percentage of Participants who Fixated (PFF), Total Fixation Duration (TFD), Time to First Fixation (TFF), and Fixation Count (FC), were measured. The survey result showed that 71% of 303 respondents preferred their lecturers to use VB during Zoom meetings, 26% preferred office VB, 25% preferred plain VB, and 20% preferred thematic VB. An experiment that is conducted to evaluate attention during online meetings with three different VBs using an eye tracker shows that attention to lecture in plain VB is the best compared to other VBs, shown by the highest value of TFF and lowest TFD and FC. Implications of the result are discussed.